RANCANG BANGUN SISTEM INFORMASI LAYANAN PENCUCIAN MOBIL DI PALANGKA RAYA BERBASIS WEB - Parhusip, Jadiaman; Sylviana, Felicia; Ariani, Rika Christalina (Universitas Palangka Raya, 2017)
Nascar car washing is a place which provides car washing service. There are some problemswhich are found in Nascar car washing. The first are is there is not any facility that can be accessedeasily in computing data. There is also not much information available about facilities provided inthat place. Before, they only use books to register and save data such as number of cars they havecleaned. They also use books to make reports of their income and outcome. Besides, they deliverinformation about facilities which they have only through mouth-to-mouth method or the costumershave to ask the owner or the staffs of the war washing service directly.Because of those problem, the researches conduct a research on an information system tohelp the cashier manages data and it is also used for costumers to find information easily. Thisresearch is entitled A Web-Based Design of Information System of Car Washing Service in PalangkaRaya.The researchers use PHP programming language, MySQL programming language and UMLDesigning Method. The result of this research is a web-based design of Information System of CarWashing Service which shows interactive menu and features which this website as a media of datamanagement, promotion media and information.